Arabidopsis Sucrose Transporter AtSUC9. High-Affinity Transport Activity, Intragenic Control of Expression, and Early Flowering Mutant Phenotype - Sivitz, Alicia B. (American Society of Plant Biologists, 2007)
AtSUC9 (At5g06170), a sucrose (Suc) transporter from Arabidopsis (Arabidopsis thaliana) L. Heynh., was expressed in Xenopus (Xenopus laevis) oocytes, and transport activity was analyzed. Compared to all other Suc transporters, AtSUC9 had an ultrahigh affinity for Suc (K(0.5) = 0.066 ± 0.025 mm). AtSUC9 showed low substrate specificity, similar to AtSUC2 (At1g22710), and transported a wide range of glucosides, including helicin, salicin, arbutin, maltose, fraxin, esculin, turanose, and α-methyl-d-glucose. The ability of AtSUC9 to transport 10 glucosides was compared directly with that of AtSUC2, HvSUT1 (from barley [Hordeum vulgare]), and ShSUT1 (from sugarcane [Saccharum hybrid]), and results indicate that type I and type II Suc transporters have different substrate specificities. AtSUC9 protein was localized to the plasma membrane by transient expression in onion (Allium cepa) epidermis. Using a whole-gene translational fusion to β-glucuronidase, AtSUC9 expression was found in sink tissues throughout the shoots and in flowers. AtSUC9 expression in Arabidopsis was dependent on intragenic sequence, and this was found to also be true for AtSUC1 (At1g71880) but not AtSUC2. Plants containing mutations in Suc transporter gene AtSUC9 were found to have an early flowering phenotype under short-day conditions. The transport properties of AtSUC9 indicate that it is uniquely suited to provide cellular uptake of Suc at very low extracellular Suc concentrations. The mutant phenotype of atsuc9 alleles indicates that AtSUC9 activity leads to a delay in floral transition.